Acetylsalicylic acid in critically ill patients: a cross‐sectional and a randomized trial. (20th June 2017) - Schoergenhofer, Christian; Hobl, Eva‐Luise; Schwameis, Michael; Gelbenegger, Georg; Staudinger, Thomas; Heinz, Gottfried; Speidl, Walter S.; Zauner, Christian; Reiter, Birgit; Lang, Irene; Jilma, Bernd
Abstract: Background: Despite decades of clinical use, the pharmacokinetics and the effects of acetylsalicylic acid (ASA) in critically ill patients remain ill‐defined. We aimed to investigate the pharmacokinetics and the effects of different ASA formulations during critical illness. Design: A cross‐sectional study and a randomized, parallel‐group trial were performed. Critically ill patients under chronic oral ASA treatment (100 mg enteric‐coated) were screened for high 'on‐treatment' platelet reactivity (HTPR) according to arachidonic acid‐induced whole‐blood aggregometry. Thirty patients with HTPR were randomized to receive 100 mg ASA intravenously, 100 mg enteric‐coated ASA bid (bis in die) or 81 mg chewable ASA ( n = 10 per group). Serum thromboxane B2 (TXB2) levels, ASA and salicylic acid levels were quantified. Results: Of 66 patients, 85% (95% confidence intervals 74–93%) had HTPR. Compared to baseline infusion of 100 mg, ASA significantly reduced platelet aggregation after 24 h to median 80% (Quartiles: 66–84%). Intake of 81 mg chewable ASA significantly reduced platelet aggregation to 75% (54–86%) after four hours, but increased it to 117% after 24 h (81–163%). Treatment with 100 mg enteric‐coated ASA bid decreased platelet aggregation after 24 h to median 56% (52–113%). Baseline TXB2 levels were median 0·35 ng/mL (0·07–0·94). Infusion of ASA or intake of 100 mg ASA bid reduced TXB2 levels to 0·07–0·18 ng/mL after 24 h, respectively. Chewable ASA reduced TXB2 levels only transiently. Pharmacokinetic analysis revealed highly variable absorption patterns of oral ASA formulations. Conclusion: There is a very high prevalence of HTPR in critically ill patients on peroral ASA therapy, caused by an incomplete suppression of TXB2 and/or by impaired absorption of ASA.